Job crafting and employees' innovative behaviour in hotels: Exploring the role of employees' psychological state and workplace gossip - Soliman, Mohammad; Anasori, Elham; Ranjan, Aditya; Obaid, Mohammad Ali (Sage Publications Ltd, 2024)
Grounded by the Job Crafting Theory, along with the JD-R model, this work examines how job crafting impacts innovative behaviour, considering the impact of psychological distress, resilience, and negative gossip at the workplace. A self-administrated questionnaire was used to collect data from employees at hotels in Antalya, Turkey, and analysed using PLS-SEM. Results showed job crafting significantly influenced both innovative behaviour and psychological distress. Individual crafting does not significantly impact resilience, but collaborative crafting substantially affects it. Psychological distress significantly impacts resilience, innovative behaviour, and negative gossip. Resilience affects both innovative behaviour and negative gossip, the latter significantly influences innovation. This research enriches theory by exploring how job crafting influences employees' innovation amidst factors (i.e., psychological distress, resilience, and gossip) in hotels. Additionally, it provides managers of hotels with strategies to enhance innovation and diminish negative workplace dynamics.
Keywords: Job crafting; psychological resilience; psychological distress; workplace gossip; innovative behaviour